What is America Eating? : Proceedings of a Symposium - National Research Council (U.S.). Food and Nutrition Board (Washington, D.C. : National Academy Press, 1986)
Explaining dietary habits, this volume examines the impact of fast-food proliferation and the changing role of women as it affects dietary behavior, and analyzes the nutritional consequences of national dietary trends. It focuses on the factors that shape eating patterns, eating trends such as snacking and food variety, nutrition policy, and more.
1. Eating patterns, nutrition, and health in the United States: The Joint Nutrition Monitoring Evaluation Committee / Susan Welsh ; Nutritional status of the U.S. population : iron, vitamin C, and zinc / Catherine Woteki, Clifford Johnson, and Robert Murphy -- 2. What factors shape eating patterns?: Introduction / Stanley R. Johnson ; Economics and nutrition / Benjamin Senauer ; The acquisition of likes and dislikes for foods / Paul Rozin and April Fallon ; Factors that shape eating patterns : a consumer behavior perspective / Kenneth J. Roering, David M. Boush, and Shannon H. Shipp -- 3. Eating trends and nutritional consequences: Introduction / Helen A. Guthrie ; Snacking and eating away from home / Karen J. Morgan and Basile Goungetas ; Variety in foods / Helen Smiciklas-Wright, Susan M. Krebs-Smith, and James Krebs-Smith -- 4. Perspectives on nutrition programs, policy, and research: Introduction / Jean-Pierre Habicht ; The role of nutrition research in policy and program / Jean-Pierre Habicht ; The food industry and nutrition / Gilbert A. Leveille ; Nutrition education / Johanna T. Dwyer ; Assessment of diet quality and the U.S. Department of Agriculture's nutrition policy and research / Betty B. Peterkin ; Legal advocacy for the hungry and manourished : how can nutrition scientists help? / Lynn Parker.
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Diet -- United States -- Congresses; Nutrition -- Congresses; Food habits -- United States -- Congresses; Food habits; Food Habits -- Congresses -- United States; Feeding Behavior; Nutrition Surveys -- Congresses -- United States; Nutrition Surveys; United States; Diet -- United States -- Congresses; Nutrition -- Congresses; Food habits -- United States -- Congresses; Alimentation -- Congrès.; Nutrition -- Congrès.; Habitudes alimentaires -- États-Unis -- Congrès.; Alimentation -- États-Unis -- Congrès.; Habitudes alimentaires; SOCIAL SCIENCE -- General; BUSINESS & ECONOMICS -- Infrastructure; Diet; Food habits; Nutrition; United States; Congress; proceedings (reports); Conference papers and proceedings; Conference papers and proceedings; Actes de congrès.